Profile of legal claims for medicines in a large municipality in the state of Bahia (International Seven Journal of Multidisciplinary, 2023)
The phenomenon of the judicialization of health in order to obtain assistance, care, procedures, health products and medicines is being incorporated into health care practices, becoming the basis for demands to obtain Fundamental Rights.